Transforming Independent Learning among Student: Perspectives on Emotional Intelligence and Parental Support - Khaulah Aisyah Putri Siswanto; Desviyanti Mukhtar; Ika Sari Dewi (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2024)
This examination plans to analyze the job of the ability to figure out individuals on a significant level and parental help for self-directed learning in Jambi City State Secondary School understudies. Examining in this review utilized an unplanned testing procedure including 502 class X and XI understudies. Information were gathered utilizing three scales, to be specific Oneself Controlled Learning Scale, The capacity to understand anyone at their core Scale and Parental Help Scale. The examination procedure utilized in this exploration is SEM investigation. The consequences of the examination show that capacity to understand anyone on a deeper level and parental help assume a critical part together in self-directed learning with a worth of .000 (p < .05). Likewise found is a R square worth of .506. The consequences of this investigation likewise discovered that the SRMR worth of .041 was more modest than .08, the NFI worth of .903 was more noteworthy than .90, and that implies that the model in this review can be supposed to be solid match, implying that ability to comprehend others more deeply and parental help together play a part in self-controlled learning among Jambi City State Secondary School understudies is 50.6%.Pengujian ini bertujuan untuk melihat kerja kemampuan mengapresiasi seseorang secara lebih mendalam dan bantuan orang tua terhadap pengendalian diri belajar pada siswa SMA Negeri Kota Jambi. Pengujian dalam review ini menggunakan prosedur pemeriksaan kebetulan yang melibatkan 502 siswa kelas X dan XI. Informasi dikumpulkan menggunakan tiga skala, yaitu Skala Pembelajaran yang Diarahkan oleh Diri Sendiri, Skala Kapasitas untuk memahami orang-orang pada intinya, dan Skala Bantuan Orang Tua. Analisis SEM digunakan sebagai metode analisis dalam penelitian ini. Hasil penelitian menunjukkan bahwa kapasitas untuk memahami seseorang secara lebih mendalam dan bantuan orang tua memainkan peran penting dalam pembelajaran mandiri dengan nilai 0,000 (p <0,05). Nilai R square sebesar 0,506 juga ditemukan. Hasil penelitian ini juga menemukan bahwa nilai SRMR sebesar .041 lebih kecil dari .08 nilai NFI sebesar .903 lebih besar dari .90 yang berarti model pada penelitian ini dapat dikatakan good fit, artinya kapasitas untuk memahami orang secara mendalam dan bantuan orang tua berperan penting dalam pembelajaran mandiri pada siswa SLTA Negeri Kota Jambi sebesar 50.6%.